CASE SERIES OF AN IMPAIRMENT DRIVEN EARLY AMBULATION PROGRAM IN CANCER PATIENTS WITH CERVICAL SPINE METASTASES AFTER PALLIATIVE SPINE SURGERY - Akira Kido; Yukako Ishida; Hideki Shigematsu; Shinji Tsukamoto; Yasuhiko Morimoto; Eiichiro Iwata; Akinori Okuda; Shingo Kishi; Hiromasa Fujii; Kanya Honoki; Yasuhito Tanaka (Journal of Cancer Rehabilitation, 2022)
Background Cervical spine metastases negatively impact quality of life (QOL) of patients with cancer. While the bene cial effects of surgery have been reported, the detailed course of functional recovery remains unclear, especially in the acute phase of rehabilitation. We previously reported on impairment-driven rehabilitation in patients with thoracic or lumbar level metastases. The present study assessed the effects of an impairment- driven strategy on the early recovery of ambulatory function in patients with cervical spine metastases. Methods We retrospectively reviewed 13 consecutive patients with cervical neoplastic spinal cord compression. The patients were those whose primary impairment with spinal instability identi ed by a multidisciplinary tumor board who underwent palliative spine surgery. In addition, we examined neurological de cits, ambulation status, pathological fracture, collapse, postoperative implant failure progress, and Barthel Index (BI). Results The average duration of ambulation was 3.75±3.92 days after surgery. One case showed collapse and two showed progressions of paralysis. However, all patients had early ambulation after surgery, except for one patient who developed postoperative cerebral infarction. The BI scores showed an improving tendency; however, the difference before and after rehabilitation was not statistically signi cant. Conclusions We reviewed the recovery course of ambulation in patients with cervical spine metastases who underwent impairment-driven rehabilitation. Combined with surgery and early mobilization, this strategy may improve the QOL of patients with cancer and cervical spine metastases.